José Eduardo Lima Pinto da Costa - Green, Andrew (The Lancet (British edition), 2022)
Legal medicine owes him the visibility and respect that was not there before his professional activity in Portugal”, said his wife, Maria José Pinto da Costa, Professor of Legal Medicine and Forensic Toxicology at the University of Porto's Biomedical Sciences Institute Abel Salazar (ICBAS). Pinto da Costa also served as a Professor of Legal Medicine at the private Portucalense Infante D Henrique University in Porto from 1986 until his death and he taught in public and private universities across the country on subjects ranging from forensic psychology to criminology and medical law. Pinto da Costa also pushed to strengthen rules for reporting intimate partner violence and to create facilities where survivors could find shelter, while also recruiting psychologists and lawyers who could offer them free support.